The Effect of Parental Attachment and Peer Rejection on Social Anxiety in Teenagers - El-Sayed, Mona; Mwangi, Grace (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2025)
Objective: This study aimed to investigate the effects of parental attachment and peer rejection on social anxiety among adolescents in Kenya.Methods and Materials: This study employed a descriptive correlational research design, involving 350 adolescent participants from Kenyan secondary schools selected randomly, with sample size determined by Morgan and Krejcie's sampling table. Data were collected using validated and reliable standard measurement tools, including the Social Anxiety Scale for Adolescents (SASA), the Parental Bonding Instrument (PBI), and the Peer Nominations Inventory (PNI). Statistical analyses included descriptive statistics, Pearson correlation coefficients, and multiple linear regression, performed using SPSS-27 software. Regression assumptions, including normality, linearity, homoscedasticity, and absence of multicollinearity, were verified and confirmed prior to analysis.Findings: Descriptive statistics indicated moderate levels of social anxiety (M = 57.34, SD = 11.42), relatively high parental attachment (M = 72.68, SD = 9.75), and moderate peer rejection (M = 24.56, SD = 6.18). Correlation analyses revealed significant negative correlations between parental attachment and social anxiety (r = -0.56, p < 0.01), and significant positive correlations between peer rejection and social anxiety (r = 0.62, p < 0.01). Regression analyses demonstrated that parental attachment and peer rejection significantly predicted social anxiety (R² = 0.41, F = 118.24, p < 0.01). Individually, parental attachment negatively predicted social anxiety (β = -0.31, p < 0.01), while peer rejection positively predicted social anxiety (β = 0.46, p < 0.01).Conclusion: Findings highlight that parental attachment significantly mitigates social anxiety, while peer rejection exacerbates anxiety symptoms among adolescents. These results underscore the importance of fostering secure parental bonds and supportive peer relationships in reducing social anxiety among adolescents. Future interventions should integrate strategies that enhance family dynamics and peer interactions to effectively support adolescent mental health.